A multicenter comparative acute myeloid leukemia study: can we explain the differences in the outcomes in resource-constrained settings?. Issue 1 (2nd January 2021) - Silveira, Douglas R. A.; Coelho-Silva, Juan L.; Silva, Wellington F.; Vallance, Grant; Pereira-Martins, Diego A.; Madeira, Maria I. A.; Figueredo-Pontes, Lorena L.; Velloso, Elvira D. R. P.; Simões, Belinda P.; Peniket, Andy; Danby, Robert; Rego, Eduardo M.; et al.
Abstract: Outcomes in acute myeloid leukemia (AML) are dependent on patient- and disease-characteristics, treatment, and socioeconomic factors. AML outcomes between resource-constrained and developed countries have not been compared directly. We analyzed two cohorts: from São Paulo state, Brazil (USP, n  = 312) and Oxford, United Kingdom (OUH, n  = 158). USP cohort had inferior 5-year overall survival compared with OUH (29% vs. 49%, adjusted- p =.027). USP patients have higher early-mortality (23% vs. 6% p <.001) primarily due to multi-resistant Gram-negative bacterial and fungal infections. USP had higher 5-year cumulative incidence of relapse (60% vs. 50%, p =.0022), were less likely to undergo hematopoietic stem cell transplant (HSCT) (28% vs. 75%, p <.001) and waited longer for HSCT (median, 23.8 vs. 7.2 months, p <.001). Three-year survival in relapsed patients was worse in USP than OUH (10% vs. 39%, p <.001). Our study indicates that efforts to improve AML outcomes in Brazil should focus on infection prevention and control, and access to HSCT.